1988
DOI: 10.3928/0147-7447-19880401-12
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Osteoblastoma of the Carpal Hamate

Abstract: A case of recurrent osteoblastoma of the hamate is reported. Curettage and bone grafting is usually followed by recurrence. Wide excision of the tumor is the treatment of choice if anatomically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…86 Osteoblastomas of the hamate have a tendency to recur after curettage and can be treated with total excision and carpal fusion involving either a vascularized iliac free flap 87 or a fifth carpometacarpal (CMC) arthrodesis. 88 Both techniques provide positive functional outcomes with no osteoblastoma recurrence at the 3- and 4-year follow-up, respectively. Daly et al reported a case of an unusual mass in the hand causing ulnar and median nerve compression treated with hamate excision and confirmed as chondroblastoma on pathology.…”
Section: Hamatementioning
confidence: 92%
“…86 Osteoblastomas of the hamate have a tendency to recur after curettage and can be treated with total excision and carpal fusion involving either a vascularized iliac free flap 87 or a fifth carpometacarpal (CMC) arthrodesis. 88 Both techniques provide positive functional outcomes with no osteoblastoma recurrence at the 3- and 4-year follow-up, respectively. Daly et al reported a case of an unusual mass in the hand causing ulnar and median nerve compression treated with hamate excision and confirmed as chondroblastoma on pathology.…”
Section: Hamatementioning
confidence: 92%